(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article deals with overcoming socio-pedagogical problems in working with gifted students. Based on pedagogical data, the author analyzes the problem on the basis of existing scientific literature and explores the specifics of overcoming socio-pedagogical problems in working with gifted students.